BREASTFEEDING SELF-EFFICACY IN WOMEN USING ASSISTIVE TECHNIQUES AND DEVICES TO ADDRESS MATERNAL AND INFANT FEEDING PROBLEMS - Hubbard, Lori J (East Carolina University, 2021)
This dissertation used the theory of planned behavior (Ajzen, 1991, 2002) and breastfeeding self-efficacy theory (Dennis, 1999) to explore relationships among breastfeeding self-efficacy and both the source and intensity of breastfeeding problems and perception of frequently used assistive techniques and devices for breastfeeding. Phase One was a qualitative, descriptive study with eight postpartum women to examine beliefs and decision-making about using a breast pump. Themes constructed to re-present the participant responses were: "Resource gathering", "Intention forming", and "Behavior navigating". Reliance on product websites and trust in online peer reviews characterized pump selection. Negotiating privacy, scheduling, and pumping necessity illustrated discussions of maternal needs at places of employment. There were minimal references to pump and milk collection safety. Phase Two used a descriptive, longitudinal, correlational survey design with 125 women who were surveyed in the first few days following birth and reassessed after 2 weeks. The perception of problems originating from either a maternal source or arising equally from a maternal and infant origin was associated with lower mean breastfeeding self-efficacy (BSE) scores on the Breastfeeding Self-Efficacy Scale -- Short Form (BSES-SF). The lowest mean BSE scores were noted in women reporting a higher intensity of breastfeeding problems, and only modest improvements in BSE were noted by the time of the follow up survey. There was no relationship between BSE and the perceived level of personal assistance needed to overcome problems. Decreased BSE from the initial to the follow up survey was noted in women who used six or more techniques and devices to overcome breastfeeding challenges. Breastfeeding self-efficacy is a modifiable attribute for nurses and lactation specialists to consider when designing programs to support breastfeeding mothers and to mitigate early weaning since high breastfeeding self-efficacy has been shown to extend breastfeeding exclusivity and duration.
Keywords: breast pump; postpartum; Breast Feeding; Infant; Female; Self Efficacy; Mothers; Surveys and Questionnaires